Implementation of Classical Guidance Services Using a Cognitive Approach Through Puzzle Media to Prevent Bullying Behavior in Grade X AV 2 Students at SMK Negeri 4 Medan - Azzahra, Dinda Aini; Deliati, Deliati; Harahap, Muhammad Fauzi (Lembaga Riset Mutiara Akbar, 2025)
This research aimed to address bullying behavior by implementing classical guidance services utilizing a cognitive approach for Grade X AV 2 students at SMK Negeri 4 Medan. A descriptive qualitative method was applied through two cycles of intervention. During the first cycle, the absence of engaging media led to low student participation and limited understanding of bullying. In the second cycle, illustrated puzzle media was introduced to increase student interest. The outcome showed a marked improvement in student engagement and their ability to explain what bullying is, its consequences, and how to prevent it. These findings suggest that incorporating puzzle-based media into classical guidance sessions can serve as an effective method to raise students’ awareness and understanding of bullying.